Chitosan Protects Immunosuppressed Mice Against Cryptosporidium parvum Infection Through TLR4/STAT1 Signaling Pathways and Gut Microbiota Modulation - Rahman, Sajid Ur; Gong, Haiyan; Mi, Rongsheng; Huang, Yan; Han, Xiangan; Chen, Zhaoguo (Frontiers in Immunology, 2022)
Cryptosporidium parvum infection is very common in infants, immunocompromised patients or in young ruminants, and chitosan supplementation exhibits beneficial effects against the infection caused by C. parvum. This study investigated whether chitosan supplementation modulates the gut microbiota and mediates the TLR4/STAT1 signaling pathways and related cytokines to attenuate C. parvum infection in immunosuppressed mice. Immunosuppressed C57BL/6 mice were divided into five treatment groups. The unchallenged mice received a basal diet (control) and three groups of mice challenged with 1×106 C. parvum received a basal diet, a diet supplemented with 50 mg/kg/day paromomycin, 1 mg/kg/day chitosan, and unchallenged mice treated with 1 mg/kg/day chitosan. Chitosan supplementation regulated serum biochemical indices and significantly (p < 0.01) reduced C. parvum oocyst excretion in infected mice treated with chitosan compared with the infected mice that received no treatment. Chitosan-fed infected mice showed significantly (p < 0.01) decreased mRNA expression levels of interferon-gamma (IFN-γ) and tumor necrosis factor-α (TNF-α) compared to infected mice that received no treatment. Chitosan significantly inhibited TLR4 and upregulated STAT1 protein expression (p < 0.01) in C. parvum-infected mice. 16S rRNA sequencing analysis revealed that chitosan supplementation increased the relative abundance of Bacteroidetes/Bacteroides, while that of Proteobacteria, Tenericutes, Defferribacteres, and Firmicutes decreased (p < 0.05). Overall, the findings revealed that chitosan supplementation can ameliorate C. parvum infection by remodeling the composition of the gut microbiota of mice, leading to mediated STAT1/TLR4 up-and down-regulation and decreased production of IFN-γ and TNF-α; and these changes resulted in better resolution and control of C. parvum infection.